Antibody responses to influenza viruses in paediatric patients and their contacts at the onset of the 2009 pandemic in Mexico - Miranda-Novales, G; Arriaga-Pizano, L; Herrera-Castillo, C; Pastelin-Palacios, R; Valero-Pacheco, N; Pérez-Toledo, M; Ferat-Osorio, E; Solórzano-Santos, F; Vázquez-Rosales, G; Espitia-Pinzón, C; Zamudio-Lugo, I; Meza-Chávez, A; et al. (Open Learning on Enteric Pathogens, 2015)
Introduction: On April 2009, the Mexican Ministry of Health received notification of cases of severe pneumonia mostly affecting young healthy people; this was the beginning of the first influenza pandemic of the 21st century. The nature of the immune response to the influenza A(H1N1)2009 pandemic strain in Mexico at the beginning of the pandemic outbreak has not been completely defined. We describe the serological response to the 2009 pandemic influenza virus in paediatric patients with influenza-like illness, their household contacts (HHCs), and exposed health-care workers (HCWs) at the beginning of the pandemic outbreak in Mexico City. Methodology: thirty pre-epidemic and 129 epidemic samples were collected and serum antibodies were measured against A(H1N1)2009 pandemic virus and two non-pandemic swine influenza viruses by an haemagglutination inhibition assay. Results: 91% (29/32) of the convalescence samples from confirmed patients had an antibody titre ≥ 10 (GMT 25), 63% (41/65) of the HHCs (GMT 12), 41% of HCWs (GMT 6) and 13% (4/30) of pre-epidemic samples (GMT 6) for the pandemic influenza virus. Of the 32 confirmed cases, 60% had an antibody titre ≥ 40 for the pandemic strain, 53% for the A/swine/Iowa(H1N1) virus (GMT 62) and 43% for the A/swine/Texas(H3N2) virus (GMT 66). Conclusion: The antibody response to 2009 pandemic influenza virus was widespread in convalescence samples from patients with confirmed pandemic influenza infection but the GMT was below the protective titre. There was no evidence that antibodies to the swine influenza viruses had cross-protective effect against the 2009 pandemic influenza virus.